(untitled) (International Journal of Current Engineering and Technology, 2013)
Petroleum based lubricants had a significant cost advantage over biolubricants and so petroleum has been the base oil of economic choice. Increase in crude oil prices, depletion of crude oil reserves and growing environmental concerns has brought in now more interest in biolubricants. Biolubricants have capability of being utilized in various industrial and maintenance applications like hydraulic fluids, metal working fluids, grease, two-stroke engine oil, concrete mould release agents, chainsaw oils and are mainly used in machinery and equipments operating in environmentally sensitive areas (e.g. agriculture and forestry machinery, jet-skis, snow mobiles etc.)Biolubricants for industrial and maintenance application, by contrast, may lead to a decrease in costs and to guarantee competitiveness. It is thus to be expected that environmentally sound applications of lubricants will be of great interest to all manufacturing companies. By the use of biolubricants, it is possible to reduce the use of petroleum based lubricants both in industrial and maintenance applications and also cut down the serious environmental problems caused.